The Impact of Online Gambling on Mental Health in New Zealand: A Comparative Study - Dash, Mark; Howard, Edward (International Journal of Scientific Research and Management (IJSRM), 2024)
Online gambling has witnessed exponential growth globally, facilitated by the proliferation of internet access and digital platforms. This phenomenon has sparked significant concerns regarding its potential impact on mental health, particularly in regions like New Zealand where gambling is popular. This paper endeavors to investigate the relationship between online gambling and mental health outcomes within the unique socio-cultural context of New Zealand, comparing these impacts with those of traditional forms of gambling.The introduction of online gambling has revolutionized the accessibility and convenience of participating in gambling activities. In New Zealand, as in many other jurisdictions, this shift has prompted regulatory responses aimed at managing potential risks while balancing consumer demand and industry growth. Despite these efforts, the pervasive nature of online gambling introduces distinct challenges that may exacerbate issues related to mental health.The study will begin by reviewing existing literature on global trends in online gambling and its documented effects on mental health. This will include an analysis of regulatory frameworks implemented in various countries to address these concerns, highlighting successes and challenges in consumer protection and harm minimization strategies. Psychological theories and models explaining addictive behaviors associated with online gambling will be explored to provide a theoretical foundation for understanding the observed impacts.A key focus of this research will be a comparative analysis between online gambling and traditional forms of gambling prevalent in New Zealand, such as land-based casinos and sports betting. By contrasting these modalities, the study aims to elucidate whether online gambling uniquely intensifies mental health risks or presents analogous challenges to traditional gambling activities.Methodologically, the study will employ a mixed-methods approach. Quantitative analysis will draw upon national gambling prevalence surveys and data from online gambling platforms to assess the prevalence of online gambling in New Zealand and profile its participants. Qualitative research will involve in-depth interviews with online gamblers and mental health professionals to capture nuanced insights into the psychological and emotional impacts experienced.Findings from the study are expected to contribute empirical evidence on the prevalence of online gambling in New Zealand, alongside comparative assessments of mental health outcomes between online and traditional gamblers. Specific risk factors associated with online gambling addiction and deterioration in mental health will be identified, shedding light on mechanisms through which these impacts manifest.The implications of these findings for policy and regulation will be discussed, emphasizing the need for adaptive strategies that safeguard mental well-being without stifling technological innovation or economic contributions from the gambling sector. Recommendations will be made for enhancing existing regulatory frameworks to ensure they adequately address the unique challenges posed by online gambling while promoting responsible gambling practices.This research seeks to advance understanding of the complex interplay between online gambling and mental health in New Zealand. By elucidating comparative impacts and exploring regulatory responses, the study aims to inform evidence-based interventions that support public health objectives while fostering a sustainable gambling environment.